Meckel’s Diverticulum Series at UCMS, Bhairahawa, Nepal - Joshi, P (Journal of Universal College of Medical Sciences, 2013)
Meckel's Diverticulum is the most common congenital malformation of the Gastrointestinal tract. It represent the patent intestinal end of the vitellointestinal duct. It occurs in 2 % of of population in autospy series and usually lie 60 cm from the Ileocaecal junction. It possesses all the three coats of intestinal wall. It has the same microscopic structure as the adjacent small bowel and it has a separate blood supply from the adjacent small bowel mesentery (the omphalomesenteric artery).1 In 20% of the cases, the mucosa contains heterotopic epithelium, namely gastric, colonic and sometimes pancreatic tissue. Although Meckel's diverticulum occurs with equal frequency in both sexes, symptoms usually resulting from the epithelium contained in the diverticulum predominantly occur in males.2 Complications develop in only 4% of patients with this malformation, with most cases presenting in childhood3. Complications of Meckel's diverticulum include hemorrhage, bowel obstruction, inflammation, and perforation. All of these complications can be challenging to diagnose because patients may present with non-specific symptoms, which produce a clinical picture that can mimic other more common gastrointestinal disorders.4 Most of the cases are diagnosed intraoperatively. Here, we present a case series of 5 patients in a year 2012 at Universal College of Medical College & Teaching Hospital, Bhairahawa, Nepal. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8767 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 56-57